Of Cosines and Polynomials

Geometry Level 4

x 3 3 x + 1 x^3 - 3x + 1 If all roots of the above third-degree polynomial can be expressed as R cos ( A D π ) R\cos\left(\dfrac{A}{D}\pi\right) , R cos ( B D π ) R\cos\left(\dfrac{B}{D}\pi\right) and R cos ( C D π ) R\cos\left(\dfrac{C}{D}\pi\right) , where

  • A , B , C , D , R A,B,C,D, R are positive integers;
  • A , B , C < D A, B, C < D ;
  • gcd ( A , D ) = gcd ( B , D ) = gcd ( C , D ) = 1 \gcd (A,D) = \gcd (B,D) = \gcd (C,D) = 1

Input A + B + C + D + R A + B + C + D + R as your answer.


The answer is 25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Pi Han Goh
Feb 1, 2021

Let x = 2 y x=2y , then 8 y 3 6 y + 1 = 0 2 ( 4 y 3 3 y ) + 1 = 0 8y^3 - 6y + 1 = 0 \quad\Leftrightarrow\quad 2(4y^3-3y) + 1 = 0

Recall the triple-angle formula, cos ( 3 A ) = 4 cos 3 ( A ) 3 cos ( A ) \cos(3A) = 4\cos^3(A) - 3\cos(A) .

Let y = cos ( z ) y = \cos(z) , then 4 y 3 3 y = cos ( 3 z ) 4y^3-3y = \cos(3z) . So, 2 cos ( 3 z ) + 1 = 0 cos ( 3 z ) = 1 2 3 z = 2 3 π , 4 3 π , 8 3 π 2\cos(3z) + 1 = 0 \quad\Leftrightarrow\quad \cos(3z) = -\frac12 \quad\Leftrightarrow\quad 3z = \frac23 \pi, \frac43 \pi, \frac83 \pi

Hence, x = 2 y = 2 cos ( z ) = 2 cos ( 2 9 π ) , 2 cos ( 4 9 π ) , 2 cos ( 8 9 π ) x\, = \, 2y \,= \, 2\cos(z) \,= \, 2\cos(\tfrac29 \pi ) , \quad 2\cos(\tfrac49 \pi ) , \quad 2\cos(\tfrac89 \pi )

The answer is R + A + B + C + D = 2 + 2 + 4 + 8 + 9 = 25 . R+A+B+C+D = 2+2+4+8+9=\boxed{25} .


Bonus question: Prove that there exists some cubic polynomial P P with integer coefficients whose real root(s) cannot be expressed as T cos ( U ) + V T \cos(U ) + V in terms of radicals T , U T,U and V . V.

K T
Feb 2, 2021

In equation x 3 3 x + 1 = 0 x^3-3x+1=0 we set x = n cos α x=n \cos α to get n 3 cos 3 α 3 n cos α + 1 = 0 n^3\cos^3α-3n\cosα+1=0

We want this to resemble the trig identity cos 3 α = 4 cos 3 α 3 cos α \cos 3 α = 4 \cos^3 α - 3 \cos α . We get the ratio for the coefficients right if we set n=2:

8 cos 3 α 6 cos α = 1 8 \cos^3 α - 6 \cos α = -1 while twice the trig identity is 8 cos 3 α 6 cos α = 2 cos 3 α 8 \cos^3 α - 6 \cos α = 2 \cos 3 α

Combine these to get cos 3 α = 1 2 \cos 3α=-\frac{1}{2} 3 α = ± 2 π / 3 + 2 k π 3α = \pm 2π/3 + 2kπ α = ± 2 π / 9 + 2 k π / 3 α = \pm 2π/9 + 2kπ/3 Taking the subset of solutions for which 0 < = α < π 0<=α<π gives x 1 = 2 cos 2 π 9 , x 2 = 2 cos 4 π 9 , x 3 = 2 cos 8 π 9 x_1=2\cos \frac {2π}{9},  x_2=2\cos\frac {4π}{9},  x_3=2\cos \frac {8π}{9}

R = 2 , A = 2 , B = 4 , C = 8 , D = 9 R=2, A=2, B=4, C=8, D=9 Submit the sum 25 \boxed{25}

Let x = R cos ( θ ) x=R\cos(\theta) , then R 3 cos 3 ( θ ) 3 R cos ( θ ) + 1 = 0 cos 3 ( θ ) 3 R 2 cos ( θ ) + 1 R 3 = 0 R^3\cos^3(\theta)-3R\cos(\theta)+1=0 \implies \cos^3(\theta)-\dfrac{3}{R^2}\cos(\theta)+\dfrac{1}{R^3}= 0 Compare with this Identity cos 3 ( θ ) 3 4 cos ( θ ) cos ( 3 θ ) = 0 \cos^3(\theta)-\dfrac{3}{4}\cos(\theta)-\cos(3\theta)=0

We get R = 2 R=2 and cos ( 3 θ ) = 1 2 θ = 2 π 9 , 4 π 9 , 8 π 9 \cos(3\theta)= -\dfrac{1}{2} \implies \theta= \dfrac{2π}{9} ,\dfrac{4π}{9} ,\dfrac{8π}{9} So x = 2 cos ( 2 π 9 ) , 2 cos ( 4 π 9 ) , 2 cos ( 8 π 9 ) x= 2\cos(\dfrac{2π}{9}), 2\cos(\dfrac{4π}{9}),2\cos(\dfrac{8π}{9})

Answer is R + A + B + C + D = 25 \color{#E81990}\boxed{R+A+B+C+D= 25}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...